Bio-development of motorway network in the Netherlands : a slime mould approach - Adamatzky, Andrew (2013)
Plasmodium of a cellular slime mould Physarum polycephalum is a very large eukaryotic microbe visible to the unaided eye. During its foraging behavior the plasmodium spans sources of nutrients with a network of protoplasmic tubes. In this paper we attempt to address the following question: Is slime mould capable of computing transport networks? By assuming the sources of nutrients are cities and protoplasmic tubes connecting the sources are motorways, how well does the plasmodium approximate existing motorway networks? We take the Netherlands as a case study for bio-development of motorways, while it has the most dense motorway network in Europe, current demand is rapidly approaching the upper limits of existing capacity. We represent twenty major cities with oat flakes, place plasmodium in Amsterdam and record how the plasmodium spreads between oat flakes via the protoplasmic tubes. First we analyze slime-mould-built and man-built transport networks in a framework of proximity graphs to investigate if the slime mould is capable of computing existing networks. We then go on to investigate if the slime mould is able calculate or adapt the network through imitating restructuring of the transport network as a response to potential localized flooding of the Netherlands.